Tunable Ag@SiO2 core–shell nanocomposites for broad spectrum antibacterial applications. Issue 38 (27th April 2017) - Isaacs, Mark A.; Durndell, Lee J.; Hilton, Anthony C.; Olivi, Luca; Parlett, Christopher M. A.; Wilson, Karen; Lee, Adam F.
Abstract : Silica encapsulated silver nanoparticle core–shell nanocomposites of tunable dimensions were synthesised via a one-pot reverse microemulsion route to achieve controlled release of Ag + ions for broad spectrum antibacterial application. Abstract : Silica encapsulated silver nanoparticle core–shell nanocomposites of tunable dimensions were synthesised via a one-pot reverse microemulsion route to achieve controlled release of Ag + ions for broad spectrum antibacterial application. Silver release rates and bactericidal efficacy against Gram-positive and Gram-negative bacteria, S. aureus and P. aeruginosa respectively, were inversely proportional to nanoparticle core diameter (3–8 nm) and silica shell (7–14 nm) thickness, and readily tuned through a facile hydrothermal etching protocol employing a PVP stabiliser to introduce mesoporosity.